Multi-Scale Structural Analysis and Hierarchical Discrimination of Natural Chitin from Diverse Biological Sources - Thaiwong, Numphon; Keawrangsi, Narinthip; Ruenphoklang, Suviporn; Kongsuk, Muntita; Phetsuk, Narawich; Vasupen, Kraisit; Rabpairee, Kanokkarn; Toommuangpak, Watcharaporn; Sinprachim, Tanayt; Lohalaksanadech, Supraewpan; Nawong, Siriwan; Kachenpukdee, Natta (Trends in Sciences, 2026)
Chitin, one of the most abundant sustainable biopolymers in nature, exhibits source-dependent structural variations that significantly influence its functional properties and applications. This study presents a multi-scale morphological analysis combined with hierarchical multivariate discrimination to comprehensively characterize chitin extracted from 5 diverse biological sources: marine mollusks (cockle, mussel), marine crustacean (shrimp), and terrestrial insects (cricket, silkworm pupa). Chitin was extracted through sequential deproteinization, neutralization, and demineralization processes. Scanning electron microscopy at 25,000× magnification revealed distinct morphological characteristics across all sources. Marine mollusk chitin exhibited highly organized fibrous (cockle) and compact plate-like (mussel) structures, while shrimp demonstrated extensive porous networks. Multi-scale analysis (5,000× - 25,000×) of insect chitin revealed a remarkable hierarchical organization with a consistent sheet-like (cricket) and wrinkled (silkworm pupa) morphologies maintained across all magnification levels, distinguishing them from marine sources. Extraction yields varied significantly (4.09% - 15.07%), with marine sources (shrimp, cockle, mussel) achieving the highest yields, correlating with their high-density structures. Degree of acetylation ranged from 68.20 ± 1.00% (cricket) to 83.39 ± 1.26% (shrimp) to 89.15 ± 1.52% (silkworm pupa), while true protein content ranged from 4.50 ± 0.34% (shrimp) to 8.19 ± 0.31% (cockle). Synchrotron Radiation-coupled Fourier-transform infrared (SR-FTIR) spectroscopy combined with hierarchical multivariate analysis (PCA) successfully discriminated all sources. Comprehensive PCA (73% variance) separated marine mollusks from other sources, but shrimp, cricket, and silkworm pupa remained overlapping. Focused PCA performed specifically on these 3 non-marine sources (71% variance) successfully resolved their subtle spectral differences. These findings establish structure-property relationships across multiple scales, providing practical guidance for selecting chitin sources for biomaterial applications. The multi-scale approach reveals that hierarchical organization in insect chitin influences extraction efficiency and molecular properties. HIGHLIGHTS Integrated multi-scale characterization (SEM, synchrotron-FTIR, PCA) provides comprehensive assessment of source-dependent chitin hierarchical organization beyond single-method approaches Distinct hierarchical features in insect chitin compared to marine sources, affecting extraction efficiency and molecular composition Non-destructive chitin source identification and property prediction using synchrotron-FTIR with PCA discrimination Targeted selection of chitin for specific biomaterial and bioengineering applications based on source-dependent structural features Comprehensive multi-scale comparison of chitin from diverse biological sources as baseline data for chitin standardization GRAPHICAL ABSTRACT